Parentification correlates experienced in childhood and adolescence from the perspective of young adults - Jolanta Żarczyńska-Hyla; Bożena Zdaniuk; Jolanta Piechnik-Borusowska; Eugenia Karcz-Taranowicz; Barbara Kromolicka (Rocznik Andragogiczny, 2017)
Parentification has also been known and studied as role reversal in family. Despite the fact that this concept entered scientific literature in the 1970’s, it has not received adequate attention and its causes and mechanisms have not been fully established. In Poland, parentification has been on the margins of psychological research and its prevalence, causes, and effects are unknown. Consequently, there is lack of practical guidelines for practitioners working with families in which role reversal might have taken place. The goal of this study is to gain insight into the prevalence, conditions, and types of parentification retrospectively reported by young adults reflecting on their family experiences in childhood and adolescence. The participants were 1045 students studying towards various teaching degrees at the University of Opole (Uniwersytet Opolski) and University of Szczecin (Uniwersytet Szczecinski). The results indicate that that parentification (or role reversal) correlates with selected sociodemographic variables, negative family life events, and with characteristics and patterns of behavior of the parents. Prevalence of parentification has also been revealed: over 70% of participants reported experiencing instrumental or emotional parentification whereas one fourth experienced a sense of injustice related to being parentified.